Step * 1 1 2 1 of Lemma arctangent-rtan


1. ∀x:ℝ(r0 < (r1 x^2))
2. ∀x:{x:ℝx ∈ (-(π/2), π/2)} (r0 < rcos(x))
3. ∀x:{x:ℝx ∈ (-(π/2), π/2)} (r0 < rcos(x)^2)
4. d(arctangent(rtan(x)))/dx = λx.(r1/r1 rtan(x)^2) (r1/rcos(x)^2) on (-(π/2), π/2)
5. {x:ℝx ∈ (-(π/2), π/2)} 
⊢ ((r1/r1 rtan(x)^2) (r1/rcos(x)^2)) r1
BY
nRMul ⌜r1 rtan(x)^2⌝ 0⋅ }

1
1. ∀x:ℝ(r0 < (r1 x^2))
2. ∀x:{x:ℝx ∈ (-(π/2), π/2)} (r0 < rcos(x))
3. ∀x:{x:ℝx ∈ (-(π/2), π/2)} (r0 < rcos(x)^2)
4. d(arctangent(rtan(x)))/dx = λx.(r1/r1 rtan(x)^2) (r1/rcos(x)^2) on (-(π/2), π/2)
5. {x:ℝx ∈ (-(π/2), π/2)} 
⊢ (r1/rcos(x)^2) (r1 rtan(x)^2)


Latex:


Latex:

1.  \mforall{}x:\mBbbR{}.  (r0  <  (r1  +  x\^{}2))
2.  \mforall{}x:\{x:\mBbbR{}|  x  \mmember{}  (-(\mpi{}/2),  \mpi{}/2)\}  .  (r0  <  rcos(x))
3.  \mforall{}x:\{x:\mBbbR{}|  x  \mmember{}  (-(\mpi{}/2),  \mpi{}/2)\}  .  (r0  <  rcos(x)\^{}2)
4.  d(arctangent(rtan(x)))/dx  =  \mlambda{}x.(r1/r1  +  rtan(x)\^{}2)  *  (r1/rcos(x)\^{}2)  on  (-(\mpi{}/2),  \mpi{}/2)
5.  x  :  \{x:\mBbbR{}|  x  \mmember{}  (-(\mpi{}/2),  \mpi{}/2)\} 
\mvdash{}  ((r1/r1  +  rtan(x)\^{}2)  *  (r1/rcos(x)\^{}2))  =  r1


By


Latex:
nRMul  \mkleeneopen{}r1  +  rtan(x)\^{}2\mkleeneclose{}  0\mcdot{}




Home Index